Youth, Christianity, and the Crisis of Civilization, 1930–1945. Issue 2 (18th June 2014) - Bergler, Thomas E.
Abstract: During the 1930s and 1940s, the Great Depression and the rise of communism and fascism in Europe convinced a broad spectrum of Americans that they were living through a prolonged "crisis of civilization" with real potential to destroy all they held dear. Meanwhile, they saw evidence that these global problems put young people especially at risk for immorality, loss of hope, and political subversion. Because the "youth problem" and the "world crisis" seemed to be inextricably linked, even the everyday behaviors of young people took on a heightened political significance in the eyes of many adults. Christian leaders from across the spectrum of churches—Mainline Protestant, Evangelical, Roman Catholic, and African American—did not just capitalize on this obsession with youth and the fate of civilization; they did all they could to fan those flames. They did so not cynically, but sincerely, believing that they could and should save the world by saving American youth. Yet these leaders were also making a bid for influence in American society and for control of the future of their churches. The resulting politicized views of youth and youth work would not only influence the outcomes of internal church battles, but they would also shape how various Christian groups responded to the Cold War.